War No More : Eliminating Conflict in the Nuclear Age - Hinde, Robert and Rotblat, Joseph; Foreword By McNamara Robert S. (London Pluto Press, 2003)
Never before have so many people worried about the effects of military conflict. At a time when terrorism is opening the way for new forms of warfare worldwide, this book provides a much-needed account of the real dangers we face, and argues that the elimination of weapons of mass destruction and of war are attainable and necessary goals. Written by Nobel Peace prizewinner and former nuclear physicist Joseph Rotblat, and biologist/ psychologist Robert Hinde, War No More provides expert insight into the nature of modern warfare -- including 'weapons of mass destruction'. Examining the key factors that are believed to contribute to conflict, they explain how best to approach a peaceful future. If war is ever to be eliminated, Hinde and Rotblat argue that we must address key issues such as the gap between rich and poor; we must have fully effective arms controls; and above all we must have better education. The authors emphasize the United Nations -- as well as non-governmental organizations, religious groups, and grassroots movements -- also have important parts to play. Joseph Rotblat was involved in the creation of the first atom bomb, but left the project during the war, when it became clear that Nazi Germany was not building its own bomb. Since the end of the Second World War he has dedicated his life to campaigning against nuclear weapons and co-founded the Pugwash conferences. Robert Hinde was a pilot in World War 2, is now a Cambridge University Professor and has written extensively on war and strategies for peace.
Include Map and Index.
Keywords: War -- War--Prevention